The mechanism for the enhanced piezoelectricity in multi-elements doped (K,Na)NbO(3) ceramics - Gao, Xiaoyi (Nat Commun, 2021)
(K,Na)NbO(3) based ceramics are considered to be one of the most promising lead-free ferroelectrics replacing Pb(Zr,Ti)O(3). Despite extensive studies over the last two decades, the mechanism for the enhanced piezoelectricity in multi-elements doped (K,Na)NbO(3) ceramics has not been fully understood. Here, we combine temperature-dependent synchrotron x-ray diffraction and property measurements, atomic-scale scanning transmission electron microscopy, and first-principle and phase-field calculations to establish the dopant–structure–property relationship for multi-elements doped (K,Na)NbO(3) ceramics. Our results indicate that the dopants induced tetragonal phase and the accompanying high-density nanoscale heterostructures with low-angle polar vectors are responsible for the high dielectric and piezoelectric properties. This work explains the mechanism of the high piezoelectricity recently achieved in (K,Na)NbO(3) ceramics and provides guidance for the design of high-performance ferroelectric ceramics, which is expected to benefit numerous functional materials.